Acetylcysteine modulates sphingolipid levels by inhibiting neutral sphingomyelinase during aging in rat tissues - Loay Khaled Hassouneh; Salameh Odatallah Aldajah; Manal Mamdouh Najdawi; Zead Helmi Abudayeh; Qais Ibrahim Abualassal; Amajad Naji aburmelah; Alaa Yahya Sirhan (Polskie Towarzystwo Farmaceutyczne, 2023)
Old-age-associated pathologies usually coincide with altered sphingolipid metabolism. Changes in the level of sphingomyelin (SM) and ceramide are largely determined by the activation of neutral sphingomyelinase (nSMase) during aging. nSMase is a key enzyme in sphingolipid turnover; it generates ceramide through the hydrolysis of SM. While N-acetylcysteine (NAC) is a powerful antioxidant which has anti-inflammatory properties and it is the precursor of glutathione (GSH). The aim of this study is to determine the impact of NAC on nSMase activity in the age-dependent changes of sphingolipid (SM and ceramide) levels and GSH content in blood serum, gastrocnemius muscle and kidney tissue of 24-month-old rats. It was found that the effect of NAC on the tissue of 24-month-old rats increased SM content; GSH content and decreased the ceramide content. The gastrocnemius muscle and kidney were the most sensitive to the effects of NAC. The results show that GSH inhibit the activity of nSMase. These results emphasize that nSMase. plays a key role in age-associated ceramide accumulation in rat tissues during aging. Furthermore, it was indicated that NAC is an effective modulator of nSMase and has pleiotropic effects that may alter sphingolipid metabolism. The nSMase inhibition enhances the benefits of NAC treatment.